PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS PROBLEM BASED LEARNING - Unik Hanifah Salsabila; Muhammad Hendriyarta; Tiara Putri Amalia; Misbahuszuhrah Ibnu Bakrin; Hendra Mahardika (MIDA : Jurnal Pendidikan Dasar Islam, 2023)
AbstractThis article discusses the problem-based learning model in Islamic religious educationusing educational technology. Problem-based learning is a learning model that directs students tosolve a problem, and the teacher has to guide the discussion so that it runs smoothly. This studyuses data collection methods with literature studies, with the hope of producing a comprehensiveunderstanding and helping readers better understand this phenomenon (learning using problembased learning using educational technology). Islamic religious learning itself is a conscious effortto understand, teach and learn about the Islamic religion. Educational technology according to thegeneral public is synonymous with technology or learning that uses technology only, buteducational technology is a tool for solving a problem in the process of teaching and learningactivities. Problem-based learning itself is a model in learning that leads to concrete and realproblems so that students can think broadly and openly. The collaboration of these two elementsleads to very effective learning, and the use of technology can facilitate the delivery of materialand receipt of material.Keywords: Islamic religious educational, Educational technology, Problem-based learningAbstrakArtikel ini membahas tentang model pembelajaran problem based learning padapendidikan agama islam dengan menggunakan teknologi pendidikan. Problem based learningadalah model pembelajaran yang mengarahkan peserta didik untuk memecahkan suatu masalah,dan guru bertugas untuk memandu diskusi agar berjalan dengan lancar. Penelitian inimenggunakan metode pengumpulan data dengan studi kepustakaan, dengan harapannyamenghasilkan pemahaman yang komprehensif dan membantu pembaca lebih memahami fenomenatersebut (belajar menggunakan problem based learning menggunakan teknologi pendidikan).Pembelajaran agama islam sendiri adalah usaha yang sadar untuk memahami, mengajar sertamempelajari tentang agama islam. Teknologi pendidikan menurut khalayak umum adalah identikdengan teknologi atau pembelajaran yang menggunakan teknologi saja, akan tetapi teknologipendidikan pada dasarnya yaitu suatu alat untuk memecahkan suatu permasalahan dalam proseskegiatan belajar mengajar. Problem based lerning sendiri adalah salah satu model dalampembelajaran yang mengarah pada permasalahan yang konkrit dan juga nyata, agar peserta didikdapat berfikir secara luas dan terbuka. Kolaborasi dari kedua unsur tersebut menyebabkanpembelajaran yang sangat efektif, dan adanya pemanfaatan teknologi dapat mempermudahjalannya penyampaian materi dan penerimaan materi.Kata kunci: Pendidikan agama islam, Teknologi pendidikan, Problem based learning